Demystifying the link between emotional loneliness and brand loyalty: Mediating roles of nostalgia, materialism and self-brand connections - Loh, Huey Shee; Gaur, Sanjaya Singh; Sharma, Piyush (Wiley-Blackwell, 2020)
This paper explores the mechanism by which consumers use their self-brand connections and emotional attachment with brands to cope with the emotional loneliness that may be caused by the absence of intimate relationships with close others. The authors also examine the mediating roles played by nostalgia and materialism on the reinforcement of brand loyalty in this process using a multi-stage model. An online survey with 456 Malaysians working adults supports all the hypotheses. Specifically, emotional loneliness has positive associations with nostalgia and materialism, both of which mediate the positive associations between emotional loneliness and self-brand connections. Self-brand connections also mediate the positive associations of nostalgia and materialism with emotional brand attachment, which in turn mediates the positive association between self-brand connections and brand loyalty. The authors discuss the theoretical contribution and managerial implications of these findings.